2018
DOI: 10.1177/0091026018819020
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in the Public Sector: Testing the Influence of Goal Orientation

Abstract: Empowerment has emerged as an important new issue in the public sector organization setting in the wake of mainstream new public management (NPM). Nevertheless, few studies in this frame have combined structural (managerial) and psychological (individual) approaches in an integrative study of empowerment. There is also a need to examine the moderating variables involved in this relationship, as well as to extend research on work motivation in public management. This study explores the effect of structural empo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 104 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…This raises the question of whether grit is weakened or strengthened by the employees' level of professionalism. An ideal goal-oriented culture provides employees with role identities that are appropriate for achieving the organization's goals and missions, and which reduce role conflicts, ambiguity, demands, and work-related stress among employees (García-Juan et al, 2019;Valmohammadi & Roshanzamir, 2015). Thus, we used professionalism and goal-oriented culture 2 as the moderators in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of whether grit is weakened or strengthened by the employees' level of professionalism. An ideal goal-oriented culture provides employees with role identities that are appropriate for achieving the organization's goals and missions, and which reduce role conflicts, ambiguity, demands, and work-related stress among employees (García-Juan et al, 2019;Valmohammadi & Roshanzamir, 2015). Thus, we used professionalism and goal-oriented culture 2 as the moderators in this study.…”
Section: Introductionmentioning
confidence: 99%
“…García-Juan, Escrig-Tena, and Roca-Puig (2018, 2019) has presented two studies of relations between structural, psychological empowerment and organizational performance. Their first research revealed that there is no confirmation on the direct link between structural and psychological empowerment (García-Juan et al, 2018) and the second study also based on empirical evidence shows that structural empowerment is positively associated with perceived organizational performance (García-Juan et al, 2019). What is more, the results uncover the role of psychological empowerment by stating that it does not mediate the abovementioned relationship, although it is a strong premise of organizational performance.…”
Section: Workplace Empowermentmentioning
confidence: 90%
“…In the scientific literature, there are three forms of empowerment are studied. Structural (also known as managerial or relational), psychological (individual) and community empowerment -all forms are captured in the empowerment theory (Zimmerman, 2000;Laschinger, Nosko, Wilk, & Finegan, 2014;García-Juan, Escrig-Tena, & Roca-Puig, 2018;Christens, 2019). All of them are important and influential in their own way but focusing on the investigation of organizational performance the structural empowerment captures the attention of the researchers the most.…”
Section: Workplace Empowermentmentioning
confidence: 99%
“…Evidently, empowerment is a topic covered the world over, and many scholars have been able to discuss the topic from a global perspective (Honold, 1997;Pelit, et al 2011;Jo and Park, 2016;Abdelhamied, et al 2017;Hirzel, et al 2017;Viveros, et al 2018;Leyer, et al 2019;García-Juan, et al 2019;Saleem, et al 2019;Berraies and Hamouda 2018;Kumar and Sajld, 2019;Manzoor, et al 2019;Nowak, 2019;Al-Omari, et al 2020), to a South African perspective (Mayeza and Maluka, 2018;de Villiers and Stander, 2011;Ronnie and Boyd, 2019;Gwinji, 2018;Dhlomo, 2018;Alsamour, et al 2018). Empowering employees is assumed to improve job satisfaction as well demonstrate that empowering employees has positive impact on apparent service quality.…”
Section: Literature Reviewmentioning
confidence: 99%